Clinical outcomes of peri-implantitis treated with bone substitute and resorbable membrane: a literature review with a systematic approach - Letícia Fernandes ALVES; Poliana Mendes DUARTE; Elizabeth Ferreira MARTINEZ; Marcelo Henrique NAPIMOGA; Marcelo SPERANDIO; Julio Cesar JOLY; Daiane Cristina PERUZZO (Faculdade São Leopoldo Mandic, 2019)
Objective: The objective of this review was to evaluate the outcomes of the treatment of peri-implant defects, using Guided Bone Regeneration. METHODS: A literature search was performed based on the PICO methodology in the PubMed/Medline, SciELO, Lilacs electronic databases, CAPES periodicals and the Cochrane Library. We included studies using bovine mineral matrix, associated to a collagen membrane for the treatment of peri-implantitis by Guided Bone Regeneration. RESULTS: Of 1,163 studies, 10 were included in this review after applying the evaluation criteria. A total of 269 implants were treated in 260 patients. The follow-up period ranged from 6 to 48 months. The studies evaluated outcome in terms of reduction in probing depth, gain of clinical attachment and healing of the bony defect. Due to the heterogeneity of the studies, it was not possible to perform meta-analysis. CONCLUSION: Treatment of peri-implant lesions with Guided Bone Regeneration is a viable modality of treatment, providing reduction in bleeding on probing, as well as gain of clinical attachment. Complete filling of the defect is, however, an unpredictable result.